2008
DOI: 10.1124/dmd.108.022988
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inhibition of Human Cytochrome P450 2B6 by Ticlopidine, Clopidogrel, and the Thiolactone Metabolite of Prasugrel

Abstract: ABSTRACT:Mechanism-based inhibition of CYP2B6 in human liver microsomes by thienopyridine antiplatelet agents ticlopidine and clopidogrel and the thiolactone metabolites of those two agents plus that of prasugrel were investigated by determining the time-and concentration-dependent inhibition of the activity of bupropion hydroxylase as the typical CYP2B6 activity. By comparing the ratios of k inact (maximal inactivation rate constant)/K I (the inactivator concentration producing a half-maximal rate of inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 26 publications
6
46
0
Order By: Relevance
“…This gives a k inact /K I ratio of 0.015 min Ϫ1 ⅐ M Ϫ1 . Therefore, 2-oxo-clopidopgrel is approximately 5-fold less efficient than clopidogrel as a mechanism-based inactivator for CYP2B6 WT, consistent with an earlier observation by Nishiya et al (2009a), who reported a decrease of nearly 12-fold in the k inact /K I ratio in human liver microsomes. Similar results were also reported for CYP2C19 that showed clopidogrel was significantly more efficient than its thiolactone metabolite in inactivating the (S)-mephenytoin 4Ј-hydroxylase activity of human liver microsomes (Hagihara et al, 2008;Nishiya et al, 2009b).…”
Section: Mechanism-based Inactivation Of Cyp2b6 Wt Bysupporting
confidence: 78%
See 1 more Smart Citation
“…This gives a k inact /K I ratio of 0.015 min Ϫ1 ⅐ M Ϫ1 . Therefore, 2-oxo-clopidopgrel is approximately 5-fold less efficient than clopidogrel as a mechanism-based inactivator for CYP2B6 WT, consistent with an earlier observation by Nishiya et al (2009a), who reported a decrease of nearly 12-fold in the k inact /K I ratio in human liver microsomes. Similar results were also reported for CYP2C19 that showed clopidogrel was significantly more efficient than its thiolactone metabolite in inactivating the (S)-mephenytoin 4Ј-hydroxylase activity of human liver microsomes (Hagihara et al, 2008;Nishiya et al, 2009b).…”
Section: Mechanism-based Inactivation Of Cyp2b6 Wt Bysupporting
confidence: 78%
“…A number of in vitro studies have provided evidence supporting this suggestion. It has been reported that thienopyridine drugs such as clopidogrel and ticlopidine are potent mechanism-based inhibitors of CYP2B6 and -2C19 (Ha-Duong et al, 2001;Richter et al, 2004;Walsky and Obach, 2007;Nishiya et al, 2009a;Nishiya et al, 2009b) and may thereby cause significant adverse drug-drug interactions. In particular, clopidogrel is highly potent and selective for inhibition of CYP2B6 in human liver microsomes, with K I and k inact values of 0.5 M and 0.35 min Ϫ1 , respectively (Richter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4) and mean binding energies of Ϫ7.67 and Ϫ7.57 kcal/ mol, respectively. These poses are consistent with 2B6-mediated oxidation of ticlopidine (Nishiya et al, 2009), and each 4-CPI contact residue listed in Table 4 falls within a 5-Å radius of the docked inhibitor. In addition, 16 poses showed alternate ligand orientations and mean energies from Ϫ7.57 to Ϫ7.27 kcal/mol.…”
Section: Resultssupporting
confidence: 53%
“…Although advances in LC-MS/MS have allowed use of lower protein concentration in the predilution step (Nishiya et al, 2009;Rowland Yeo et al, 2011), most of the two-step studies reported in the literature have used a high enzyme concentration in the preincubation to facilitate a significant dilution into the final incubation. Under these conditions, the assumption of EϽ ϽI can be compromised, and rapid metabolite production, which is not accounted for in the data analysis process, may lead to significant bias in parameter estimates.…”
Section: Discussionmentioning
confidence: 99%